The Impact of Chinese Whisper Game towards EFL Young Learners’ Vocabulary Mastery - Aniswatun Nafisah; Choiril Anwar; Hartono Hartono; Riana Permatasari (Journal of Advanced Multidisciplinary Research, 2022)
The purpose of this research was to find out whether the use of Chinese whisper game was effective to enhancein enhancing vocabulary mastery of young learners of the fifth graders of MI Nurul Huda Sidokumpul. The method of this research was quasi-experimental design because the researcher did not randomize on the sample. The sample of this research consisted of 25 students of class VA as the experimental group and 22 students of class VB as the control group. The researcher used pre-test and post-test for the control group and experimental group to collect the data. The researcher used SPSS v.16.0 software program to analyze the data. The researcher used three steps in this research. They were: pre-test, treatment, and post-test. The result of the pretest and post-test of the experimental group were 58.76 and 91.84, while the result of the pre-test and post-test of the control group were 60.36 and 70. 27. The result of the analysis showed that sig (2-tailed) was 0.000 (or <0.05. It means that there was a significant difference between the two means of post-test. It was concluded that H0 was rejected and H1 was accepted. Therefore, using the Chinese Whisper Game was effective to enhance the vocabulary mastery of young learners.Â